Leucine does not affect mechanistic target of rapamycin complex 1 assembly but is required for maximal ribosomal protein s6 kinase 1 activity in human skeletal muscle following resistance exercise - Apró, William; Moberg, Marcus; Hamilton, D Lee; Ekblom, Björn; Rooyackers, Olav; Holmberg, Hans-Christer; Blomstrand, Eva (The FASEB journal, 2015)
We examined how the stimulatory effect of leucine on the mechanistic target of rapamycin complex 1 (mTORC1) pathway is affected by the presence of the remaining essential amino acids (EAAs). Nine male subjects performed resistance exercise on 4 occasions and were randomly supplied EAAs with leucine, EAAs without leucine (EAA-Leu), leucine alone, or flavored water (placebo; control). Muscle biopsies were taken from the vastus lateralis before and 60 and 90 min after exercise. Biopsies were analyzed for protein phosphorylation, kinase activity, protein-protein interactions, amino acid concentrations, and tracer incorporation. Leucine alone stimulated ribosomal protein s6 kinase 1 (S6K1) phosphorylation ∼280% more than placebo and EAA-Leu after exercise. Moreover, this response was enhanced by 60-75% after intake of EAAs compared with that of leucine alone (P < 0.05). Kinase activity of S6K1 reflected that of S6K1 phosphorylation; 60 min after exercise, the activity was elevated 3.3- and 4.2-fold with intake of leucine alone and with EAAs, respectively (P < 0.05). The interaction between mammalian target of rapamycin and regulatory-associated protein of mammalian target of rapamycin was unaltered in response to both resistance exercise and amino acid provision. Leucine alone stimulates mTORC1 signaling, although this response is enhanced by other EAAs and does not appear to be caused by alterations in mTORC1 assembly.